Aplicativo Python para suporte pedagógico no cálculo de equações de estado cúbicas - Moraes, Artur Amaral Corrêa de (2022)
Science and engineering have changed in recent decades with technological development and also the advent of programming. Chemical Engineering and its activity was impacted both in industrial activity, as well as in scientific research and teaching, with the emergence of increasingly modern software capable of solving problems through computational calculations. In this context, traditional teaching gains possibilities with the addition of other learning strategies. Among the areas of knowledge of Chemical Engineering, the discipline of Chemical Thermodynamics was chosen to insert the use of an auxiliary program in the calculation of Cubic Equations of State. These equations describe and predict properties of mixtures of liquids and gases from properties such as temperature, pressure and volume, characterizing a thermodynamic state, helping, for example, in the design of the most diverse industrial equipment. Cubic Equations of State such as Van der Waals, Soave-Redlich-Kwong, PengRobinson, among others, were selected, covering the widest possible range of the aforementioned physical properties, making use of different parameters and considerations and encompassing the list of fluids most used in the industry. For this, the Python computational language and open source libraries such as Thermo and Tkinter will be used, references in their areas, to build a graphical interface that allows the user to obtain intermediate results of their problems, specific values where state changes or critics points occur, graphics, etc. and can compare the values obtained according to the chosen model and verify the associated error, for example, when selecting an inappropriate range for the equation.